ABO AND RHESUS BLOOD GROUP DISTRIBUTION AMONG INDEGEOUS PEOPLE IN SOUTH SUMATERA - Elfa Nur Hikma; Abdul Mutholib; Ardiya Garini (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Palembang, 2021)
Background: ABO and Rhesus blood group systems are genetic markers that are useful in the study of human populations, in addition, they play an important role in incompatible blood and marital transfusions. The purpose of this research was to describe ABO And Rhesus Blood Group Systems of Health Polytechnic Palembang Students as Indegeous People in South Sumatera of 2019 Methods: The respondents were 187 students of Palembang Health Polytechnic. This type of research was descriptive with a cross sectional approach. Taken by total sampling technique Results:The results showed Komering tribal students were A (38.1%), B (23.8%), O (28.6%), and AB (9.5%). The Palembang tribe A (26.8%), B (32.1%), O (30.4%), and AB (10.7%). The Gumai tribe A (66.7%), B (0.0%), O (33.3%), and AB (0.0%). The Semendo tribe A (33.3%), B (33.3%), O (33.3%), and AB (0.0%). The Lintang tribe A (33.3%), B (0.0%), O (33.3%), and AB (33.3%). The Kayu Agung tribe A (27.3%), B (9.1%), O (45.5%), and AB (18.2%). The Lematang tribe A (28.6%), B (42.9%), O (14.3%), and AB (14.3%). The Ogan tribe A (30.0%), B (20.0%), O (37.5%), and AB (12.5%). The Pasemah tribe A (33.3%), B (33.3%), O (33.3%), and AB (0.0%). The Sekayu tribe A (29.4%), B (35.3%), O (29.4%), and AB (5.9%). The Rawas tribe A (50.0%), B (0.0%), O (50.0%), and AB (0.0%). The Banyuasin tribe A (30.0%), B (30.0%), O (20.0%), and AB (20.0%). All samples had Rhesus positive (+) blood group with a percentage of 100.0% Conclusion: Therefore, it can be concluded that the highest percentage of the distribution is blood group O, while the lowest is blood blood group AB, all of them are Rhesus positive (+)